2013
DOI: 10.1111/bph.12093
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation: a potential therapeutic strategy in oesophageal cancer

Abstract: Raised intracellular iron has been identified as a potential aetiological factor in the development of several epithelial malignancies, including those of the gastrointestinal tract. The mechanism behind this increase is thought to include disorders of iron uptake and storage. Several iron chelators have been identified as potential anti-tumour agents, with much work undertaken to ascertain the exact mode of action. Despite this, there is little known about the role that these drugs play in the cellular iron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Bacterial biosynthesis of siderophores (iron-chelating compounds) was associated with higher EAC risk. While excessive iron may promote carcinogenesis (47) and iron chelation has been considered as a potential EAC therapy (48), iron is an essential trace element with deficiency leading to inflammation (49). Bacterial siderophore synthesis may upset iron homeostasis, and thus might increase EAC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial biosynthesis of siderophores (iron-chelating compounds) was associated with higher EAC risk. While excessive iron may promote carcinogenesis (47) and iron chelation has been considered as a potential EAC therapy (48), iron is an essential trace element with deficiency leading to inflammation (49). Bacterial siderophore synthesis may upset iron homeostasis, and thus might increase EAC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have indicated that DFO has anti-cancer activity against some types of cancer cells. DFO has potent effects on human neuroblastoma cells, esophageal cancer cells and leukemic by inhibition of proliferation and differentiation [ 134 , 135 , 136 ]. In a clinical study, the overall response rate was 20% for hepatocellular carcinoma with DFO treatment [ 137 ].…”
Section: Therapeutic Opportunities For Cancer Based On Altered Iromentioning
confidence: 99%
“…Researches have demonstrated that DFX could reduce cellular viability and proliferation in vitro, including small-cell lung cancer, oesophageal cancer and gastric cancer. Moreover, oral DFX was able to significantly suppress tumor growth in xenograft models [ 136 , 139 , 140 ]. Similar to the mechanism of DFO, DFX inhibits the cell cycle through reducing cellular iron acquisition and intracellular iron levels [ 136 , 139 ].…”
Section: Therapeutic Opportunities For Cancer Based On Altered Iromentioning
confidence: 99%
“…Clinical trials have confirmed that some cancers, as neuroblastoma and leukaemia, are sensitive to DFO therapy while normal tissues are affected only in little extent (Desoize, 2004). Nowadays, iron depletion has been proposed for the treatments of several kinds of cancers and metastatic progression (Kovacevic, 2012;Keeler and Brookes, 2013;Richardson et al, 2013;Torti and Torti, 2013). A triapine derivative, di-2-pyridylketone-4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC) is currently under preclinical evaluation (Lane et al, 2014).…”
Section: Ironmentioning
confidence: 99%